Assessing digital library acceptance by postgraduate students: a proposed framework - Pathan, Abida Kanwal; Chandio, Shahmurad; Hussin, Husnayati; Shah, Asadullah (University of Sindh, Jamshoro, 2017)
A collection of information along with related services managed and stored in the digital formats for accessing over a digital network in called digital library. The study aims to calculate the acceptanece of digital library program initiated by Higher education commission of Pakistan. Higher education commission is monitoring body that overlooks the higher education institutions and provides them with required facilities, equipment and services. One of its biggest services is digital library program, an outstanding national level digital library in Pakistan. For the sake of encourage the research culture and improve the digital infrastructure nation-wide, digital library is introduced. The study is based on a reviewing relevant literature on the subject to evaluate successes of digital library project and assessing its acceptance in perspective of user particularly research students of various universities and to provide theoretical framework towards acceptance of digital library by research students.